Feliks Nowowiejski on School of Church Music in Regensburg - Dulisz, Ilona (Studia Warmińskie, 2014)
School of Church Music in Regensburg founded in 1874 by F.X. Haberl, from the beginning of its existence has gained an international importance, especially in the Catholic countries of Europe. In this place many prominent religious composers were educated including F. Nowowiejski, in the year 1900 participant 26 – of that edition of church music course. The composer's stay in Regensburg is documented by extremely flattering certificates issued by the local masters Haberl and Haller and a series of four articles entitled About the significance of Regensburg for a church-music movement, appearing in “Church Music” in the years 1933-1934 by F. Nowowiejski. The articles contain valuable information about the history of the school, ideas promoted by it and their graduates. They feature personal reflections of the composer associated with the atmosphere of the city, its tradition, and the sound of music.